Cenopoesia, a arte em todo ser: das especificidades artísticas às interseções com a educação popular - Dantas, Maria Josevânia (2015)
This paper brings up an important issue in popular culture, but rarely addressed in the academic setting: the “cenopoesia”. The phenomenon stands in the study anchored by the themes of art and popular education. It aims at understanding and interpreting the “cenopoesia” as artistic specificity to unravel whether we can identify it as an expression of popular education. Methodologically, the study has a qualitative approach, referenced by the dialectical method and has an exploratory purpose. As investigative tools, we use the literature and documents, participant observation and open questionnaire applied to ten (10) “cenopoetas”, analyzed in the light of the technique content analysis. The research highlights the artistic nature of “cenopoesia” from the historical analysis of the concept of art emphasizing its hybrid aspect and its open work perspective arguing that we can all live and make art. Strives to learn the meaning, of its “cenopoesia” history, how it is, constituted and how it expresses itself. Uses historical review and the foundations of popular education by examining the perceptions of “cenopoetas” as for their views on “cenopoesia” and their approaches to popular education. Finally, it presents some interpretations of the “cenopoetas” acting weighted by an analysis between theory and practice. The study reveals that “cenopoesia” is guided in an artistic perspective with hybrid basis, in which its actions result from an open and democratic creation process accepting all forms of expression along its manifestations, knowledge, experience and languages through an autonomous and affective dialogue. It searches for overcoming the artistic exceptionality in order to restore the ontological creative condition of the people. Its practice is characterized by the articulation of human repertoires and its compositions are made through various modalities. The performance of “cenopoetas” legitimizes “cenopoesia” as knowledge built in praxis, from experiences and life experiences. The "cenopoesia" emerges in a popular background, adopted by people who are involved and active along the transformation of the environment where they live. It appears as a movement in defense of the creative freedom, communicative democratization, human emancipation, empowered by the inventive form of resistance created to highlight its presence in history.